1996
DOI: 10.1007/bf02369413
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational investigation of heat fluxes in a supersonic diffuser

Abstract: The internal structure of a turbulent flow in a boundary layer brings about an expressed two-layer character of flow with respect to the characteristic relaxation time of perturbations. The different relaxation times of perturbations in the internal and external parts of a boundary layer are not taken into account by the Boussinesq hypothesis, in which turbulence is determined by the usual law for a viscous liquid of dependence of stresses on the strain rate, which differs only in the renormalized viscosity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Cooling of the supersonic diffuser has been studied. 14,15) Supersonic combustion gas flow decelerates to subsonic through the pseudo-shock. The general estimation formula for heat transfer is not effective in the pseudo-shock region.…”
Section: Pseudo-shock In Diffusermentioning
confidence: 99%
“…Cooling of the supersonic diffuser has been studied. 14,15) Supersonic combustion gas flow decelerates to subsonic through the pseudo-shock. The general estimation formula for heat transfer is not effective in the pseudo-shock region.…”
Section: Pseudo-shock In Diffusermentioning
confidence: 99%
“…Studies have been conducted for prediction of the heat transfer in supersonic diffusers. Back et al 2) and Zaikovskii et al 3) reported on heat transfer in supersonic diffusers. Back and Cuffel gave an empirical equation between wall static pressure and heat transfer coefficient in the shock wave impingement on the turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%